Strongyloides Hyper-Infection Syndrome and Ciliocytophthoria Mimicking Balantidium coli - Roy, Moni; Ahmad, Sharjeel; Sarwari, Arif (European Journal of Case Reports in Internal Medicine, 2021)
Ciliocytophthoria is a phenomenon where degenerated cells in infections or malignancy can present as ciliated cells on microscopy and so may be confused with ciliated parasitic infection. We present an interesting case of recurrent shortness of breath, misdiagnosed as chronic obstructive pulmonary disease exacerbations leading to unnecessary exposure to antimicrobials and steroids. The case was diagnosed as Strongyloides hyper-infection syndrome. Another finding worth mentioning was that ciliated cells noted on broncho-alveolar lavage were thought to be a co-infection with Balantidium coli but were later confirmed as ciliocytophthoria.